Implementation of a Teacher Performance Assessment System Based on the Ruang GTK Platform to Strengthen Teaching Staff Competence at SMPN 2 Karangrejo, Magetan Regency - Lutviana (International Journal of Science and Environment (IJSE), 2026)
This study examines the implementation of a teacher performance assessment system using the GTK Room platform at SMPN 2 Karangrejo, Magetan, and its impact on strengthening teacher competence. The conventional evaluation system, being administrative, lacked feedback and integration with professional development, especially in semi-rural schools with limited training access. A quantitative survey was conducted with 28 respondents (25 teachers and 3 school leaders) using questionnaires, classroom observations, and platform documentation. Data were analyzed with descriptive statistics and multiple linear regression. Implementation satisfaction scored 8.3 out of 10. Pedagogic competence improved most substantially: 85.7% of teachers progressed in designing innovative, student-centered learning, with learning quality scores rising significantly by 23.4%. Digital literacy recorded the highest growth rate (92.9%), while professional competence and independent learning culture also strengthened significantly. Regression analysis showed principal support as the strongest success predictor (β=0.62), followed by technological infrastructure readiness (β=0.48) and teacher collaboration (β=0.41). Major obstacles—internet instability and digital literacy gaps between senior and junior teachers—require infrastructure strengthening and differentiated mentoring. In conclusion, shifting from administrative to digital platform-based assessment effectively promotes sustainable teacher professional development, even in resource-limited settings, provided there is visionary leadership and adequate mentoring support. These findings recommend accelerating digital teacher performance management in regions as a comprehensive, inclusive, and sustainable strategy for education quality equity, and they can serve as a replicable model of good practice for schools with similar characteristics.